Are we right to blame it all on colonialism?: The subject of history and gender in schools in a Malawian context - Alinane Priscilla Kamlongera Katenga-Kaunda (Journal of Comparative Social Work, 2015)
The study on the history school subject showed that any reenactment of the history discipline should include the reinterpretation of identities from a historical perspective, and this reinterpretation should start with colonial history because this is where it all began. A different approach to history will have positive implications on society’s view of gender, as it will encourage the inclusion of devalued categories such as women, black women and third-world women. But does this mean that colonialism is fully to blame for all the gender issues, as is the case within the Malawian history syllabus? This paper explores the influence of colonialism on the history/social and environmental sciences primary school subject.